Metamorphic reactions and preliminary P-T estimates of ultrahigh-temperature mafic granulite from Tonagh Island in the Napier Complex, East Antarctica - Tunogae, Toshiaki; Osanai, Yasuhito; Toyoshima, Tsuyoshi; Owada, Masaaki; Hokada, Tomokazu; Crowe, Warwick A. (National Institute of Polar Research, 1999)
P(論文) Metamorphic reactions and P-T conditions of mafic granulites from Tonagh Island in the Archean Napier Complex were examined to evaluate the nature of mafic granulite which has suffered ultrahigh-temperature (UHT) metamorphism. Although a peak mineral assemblage is preserved in plagioclase-orthopyroxene-clinopyroxene mafic granulites, initial mineral chemistry was completely reset by retrograde metamorphism. Evidence of UHT metamorphism was therefore inferred using lamella-bearing pyroxenes as 900 to 980℃. Hornblende-quartz, biotite-quartz, and garnet-hornblende-quartz coronas around ortho- and clinopyroxenes in two-pyroxene mafic granulites are typical evidence of retrograde metamorphism in amphibolite-facies conditions. The textures suggest that the retrograde event took place in the presence of H_2O-bearing fluid. Garnet-quartz corona after pyroxenes is an another predominant texture of retrograde metamorphism throughout the studied area. As the corona is characterized by anhydrous mineral assemblages, we suggest that retrograde infiltration of H_2O-bearing fluid is a local event. The corona texture suggests that retrograde metamorphism has taken place almost isobarically, because a univariant line of the corona-forming reaction shows a gentle slope in P-T space. The isobaric cooling temperature (650-700℃ at 6.5-8.0 kbar) is, however, significantly lower than the previously reported cooling temperature of approximately 950℃ subsequent to UHT metamorphism. Mafic granulites therefore preserve the second isobaric cooling event, which is distinguished from high-temperature isobaric cooling. The mafic granulites were subsequently intruded by mafic dykes which were also metamorphosed. P-T conditions recorded in the rocks are 630-670℃ at 6.4-8.2 kbar, consistent with the retrograde event of host mafic granulites. The event marks the last stage of regional metamorphism recorded in mafic granulites. departmental bulletin paper